Towards an Asymmetric Organocatalytic α-Azidation of β-Ketoesters - Maximilian Tiffner; Lotte Stockhammer; Johannes Schörgenhumer; Katharina Röser; Mario Waser (Molecules, 2018)
Detailed investigations concerning the organocatalytic (asymmetric) α-azidation of prochiral β-ketoesters were carried out. It was shown that the racemic version of such a reaction can either be carried out under oxidative conditions using TMSN3 as the azide-source with quaternary ammonium iodides as the catalysts, or by using hypervalent iodine-based electrophilic azide-transfer reagents with different organocatalysts. In addition, the latter strategy could also be carried out with modest enantioselectivities when using simple cinchona alkaloid catalysts, albeit with relatively low yields.